THE IMPLEMENTATION OF “THINK PAIR SHARE” FOR TEACHING SPEAKING DESCRIPTIVE TEXTS TO THE EIGHTH GRADERS (RETAIN, 2016)
THE IMPLEMENTATION OF “THINK PAIR SHARE” FOR TEACHING SPEAKING DESCRIPTIVE TEXTS TO THE EIGHTH GRADERS Melindah Rosa Dewi English Education Department, Language and Arts Faculty, Surabaya State University Email: melinda_rosa19@yahoo.com Abstract Speaking is one of language skills that should be mastered by the students. Speaking in foreign language seems much harder than that of writing and reading. The teacher should find an appropriate and interesting technique for teaching speaking in order to reach the goal of learning and to make the students interest in speaking. Think pair share is the technique that can help the students to become more active in teaching and learning process. The purpose of the research is to investigate the implementation of think pair share for teaching speaking descriptive text to the eight graders and the students’ opinion. This research used descriptive qualitative research. The subject of the study was the eighth graders of SMPN 1 Porong. The data in this research were the result of observation checklist and questionnaire. The result of observations showed that the teacher followed the procedure of think pair share technique in teaching speaking well. And the result of questionnaire that given to the students showed positive effect. In conclusion, think pair share technique is appropriate for teaching speaking descriptive text to the eight graders Keywords: Speaking Ability, Teaching speaking, Descriptive text, Think pair share Abstrak Berbicara merupakan salah satu kemampuan berbahasa yang harus dipelajari oleh siswa. berbicara bahasa asing lebih sulit dibandingkan dengan menulis dan membaca. Guru harus menemukan teknik yang cocok dan menarik untuk mengajar berbicara agar mencapai tujuan dari pembelajaran dan untuk membuat siswa tertarik untuk berbicara. Think pair share merupakan teknik yang bisa membantu siswa menjadi lebih aktif dalam proses belajar mengajar. Tujuan dari penelitian ini adalah untuk meneliti penerapan teknik think pair share untuk pengajaran berbicara teks deskriptif untuk siswa kelas delapan dan pendapat siswa. Penelitian ini menggunakan penelitian deskriptif kualitatif. Subyek dari penelitian ini adalah siswa kelas 8 di SMPN 1 Porong. Data dari penelitian ini adalah hasil observasi dan kuisioner.Hasil dari penelitian menunjukan bahwa guru menerapkan langkah-langkah dari teknik think pair share untuk pengajaran berbicara sudah baik. Dan hasil dari kuisioner yang telah diberikan kepada siswa menunjukan efek yang positif. Kesimpulannya, think pair share teknik adalah teknik yang sesuai untuk pengajaran berbicara teks deskriptif untuk kelas delapan. Kata Kunci: Kemampuan berbicara, Pengajaran berbicara, Teks deskriptif, Think pair share